SDG11, Sustainable cities and communities - GÜRSOY HAKSEVENLER, BETÜL HANDE (Routledge, London/New York, 2022)
Attainment of SDG 11 targets will depend crucially on the realisation of other SDGs, especially SDG 7, which is to ensure access to affordable, reliable, sustainable and modern energy for all. Turkey is highly dependent on imported fossil fuels, a leading cause of the worldwide ecological crisis while having a significant renewable energy potential. Thus, this chapter aims to develop arguments that could feed into policy proposals to increase the share of renewable energy use in Istanbul, Turkey, towards the attainment of SDG 11 targets. For this purpose, face-to-face interviews were conducted with local governments and private sector representatives, and secondary sources were used. Results indicate that although Istanbul has a strong wind and solar energy potential, these sources are not used efficiently due to dependence on fossil fuels, lack of local renewable energy plans and insufficient geographic area in the city. Energy generation from waste, rooftop solar-energy systems and micro-wind energy systems are also appropriate for Istanbul. The facilitators are the risk tolerance of companies, improvement of the incentive mechanisms and domestic production. On the other hand, financial problems, uncertain/unclear regulations, bureaucratic difficulties and lack of networks and infrastructure emerged as the main obstacles.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Kamu Yönetimi; Kentleşme ve Çevre Sorunları; Çevre Mühendisliği; Çevre Bilimleri; Mühendislik ve Teknoloji; Social Sciences and Humanities; Political Science; Public Administration; Urbanization and Environmental Problems; Environmental Engineering; Environmental Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Çevre / Ekoloji; Sosyal Bilimler Genel; ÇEVRE BİLİMLERİ; SİYASET BİLİMİ; KAMU YÖNETİMİ; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Social Sciences (SOC); ENVIRONMENT/ECOLOGY; SOCIAL SCIENCES, GENERAL; ENVIRONMENTAL SCIENCES; POLITICAL SCIENCE; PUBLIC ADMINISTRATION; Su Bilimi; Siyasi bilimler ve Uluslararası İlişkiler; Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; Fizik Bilimleri; Yaşam Bilimleri; Aquatic Science; Political Science and International Relations; Nature and Landscape Conservation; Environmental Science (miscellaneous); Social Sciences & Humanities; Physical Sciences; Life Sciences